2007
DOI: 10.1177/0143831x07073027
|View full text |Cite
|
Sign up to set email alerts
|

Are Works Councils and Joint Consultative Committees a Threat to Trade Unions? A Comparative Analysis

Abstract: This article assesses whether the operation of works councils or joint consultative committees (JCCs) is inimical to unionization in different business systems. An extensive transnational survey reveals that both works councils and JCCs are positively associated with a union presence; there is no evidence from this sample that either is used to any significant extent as a substitute for unions. The finding holds true irrespective of business system. Its implications for industrial relations actors are examined. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 46 publications
2
56
0
1
Order By: Relevance
“…Whitley 1999;Brewster et al 2007a). However, while Mark Harcourt and Geoffrey suggest that training is likely to be correlated with a reduced willingness to make redundancies, this association was only weak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitley 1999;Brewster et al 2007a). However, while Mark Harcourt and Geoffrey suggest that training is likely to be correlated with a reduced willingness to make redundancies, this association was only weak.…”
Section: Resultsmentioning
confidence: 99%
“…Stronger forms of employee participation would be representative: as employees are represented as a collective, their combined voice will be stronger, whilst individual employees are more likely to enjoy a greater protection from victimization (Harcourt, Harcourt and Wood 2004;Hirschman 1970). Brewster et al (2007a) found that forms of representative participation are likely to be encountered together, i.e., works councils are more likely to be encountered in unionized workplaces. Gooderham, Nordhaug and Ringdal (1999) argue that certain forms of direct participation may be similarly encountered together (c.f.…”
Section: Key Practices and Likely Correlationsmentioning
confidence: 99%
“…Sector is included since it is likely that the nature of the relationship between employers and employees will differ between sectors (Brewster et al, 2007a). It is also likely that public sector organizations will be more collaboratively focused.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging literature on the relative extent of employee voice in different capitalist archetypes, based on firm-level micro evidence (Brewster et al, 2007a;Goergen et al, 2009). In contrast, we focus here on relative propensity to exit, and other indicators of collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that American companies could learn the advantages of the Continental European model, which supports the stronger involvement of workers in strategy construction. It is also possible that in the long run both local management and trade unions may seek to expand their international networks and deploy international comparisons to influence organizational change and restructuring, or indeed seek European-level accommodations on some issues which reach across borders by using mechanisms as European works councils (Arrowsmith and Marginson, 2006;Brewster et al,2007;Huzzard and Docherty,2005). These are interesting hypotheses which need a longitudinal research design which would focus on learning and bargaining processes in mergers and acquisitions, but these processes did not take place under the time span of research in which this article is based.…”
Section: Discussionmentioning
confidence: 99%